PECULIARITIES OF VALUES AND THEIR BEHAVIOURAL EXPRESSION IN THE ADOLESCENTS LIVING IN FAMILIES AND FOSTER HOMES - LEPEŠKIENĖ, Vitalija; ZENKEVIČ, Jolanta (Socialinė teorija, empirija, politika ir praktika, 2015)
The problem of adolescents adopting moral values is widely discussed in the scientific literature and many research studies have been conducted to ascertain the value priorities of the teens. However, most of the research studies are limited to elucidating the hierarchy of the values of the subjects, regardless of their life experience. The present article deals with the issue of values of the adolescents living in families and foster homes. The goal of our research is to elucidate the values and their behavioural manifestation of teenagers living in families and compare them with those of teenagers living in foster homes.103 teenagers (53 males and 50 females, 62 living in the families and 41 living in the foster homes) were surveyed using a questionnaire. The questionnaire consisted of two parts. In the first part the subjects were given a list of 18 values to be ranged according to the importance for them. The values had to be evaluated in the scale of 1–6. The second part of the questionnaire was designed to clarify the probability of the behavioural manifestation of corresponding values. The subjects had to rate the probability of their behaviour in given situations in the scale of 1–6, demanding for an expression of a certain value.The research proved that the most important values for the teenagers were health, family, true friendship and true love, while religion, social acknowledgement and beauty were least important. Values of true friendship, freedom, honesty and health appeared to be the least internalized, since subjects did not tend to base their behaviour on these values. Meanwhile, such values as family, tolerance, responsibility, courage, material wealth and social acknowledgement appeared to be strongly expressed in the subjects’ behaviour.The comparison of the results shown by teenagers living in families and foster homes revealed differences between the two groups: those living in families more often tend to manifest in their behaviour the values of education, responsibility, sensitivity, material wealth and religion, while those living in foster homes more often base their behaviour on honesty, activity, and social acknowledgement. The subjects of both groups equally express the values of true friendship, family and true love. Female subjects living in families more often behaviorally express sensitivity, creativity, and activity than those living in foster homes. Male subjects living in families more often than those living in foster homes manifest in their behaviour religious values, while males living in foster homes tend to express the values of true love, activity, and social acknowledgement.
Keywords: adolescence’s values; value based behavior; foster homes